Larangan Pendidikan Formal bagi Kaum Perempuan di Afghanistan: Tinjauan Hadis al- Bukhari Nomor Indeks 7310 tentang Kesetaraan Gender - Rodina Billah; Andris Nurita; Muhid Muhid (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
Afghanistan is one of the countries with relatively high cases of discrimination against women. This is due to the implementation of the Islamic shari'a system of government imposed by the Taliban based on their own understanding. As well as textual interpretation of some of the postulates of Islamic teachings. So that the existence of the role of women is increasingly cornered. One of the Taliban's policies, which is considered to violate human rights, is the prohibition of higher education for women in Afghanistan. This problem raises the negative stigma of